THE EFFECTIVENESS OF DRUG ADDICTION TREATMENT OF 8 SESSIONS MODIFIED MATRIX MODEL - เอี่ยมสุขวัฒน์, ไกรวุฒิ (Primary Health Care Journal (Northeastern Edition), 2022)
This research was a Quasi experimental research. To study the effectiveness of 8 sessions modified Matrix model at Khon Kaen hospital. Patients were 331 users, addicts from Department of Probation in Khon Kaen. Patients were treated by 8 sessions modified Matrix model and urine test for drugs. The tool used is 8 sessions modified Matrix model. The data collection tools included the research participants general data record form, treatment record form, Alcohol Smoking and Substance Involvement Screening Test V.2 (ASSIST V2). Analyze data by descriptive statistics, inferential statistics, statistics in the proportional test were Z test and 95% CI. The results showed that participants consisted of 331 people, mostly males 88.2%, average age 29.87 years (SD = 9.03). The type of drug used mostly was methamphetamine 86.1%. The results of treatment were found to be successful 79.8% (95% CI : 75.4 to 84.1). Factors that were significantly associated with discontinuation of amphetamine (p-value <0.05) were (i) age of first drug use (Crude OR = 1.04 , 95% CI : 1.01 to 1.09, p-value = 0.042). (ii) Duration of use of the primary drug (Crude OR = 0.95, 95% CI : 0.90 to 0.99, p-value = 0.032).